Unveiling the CoA mediated salicylate catabolic mechanism in Rhizobium sp. X9. Issue 3 (28th June 2021) - Zhou, Yidong; Gao, Siyuan; Zhang, Mingliang; Jiang, Wankui; Ke, Zhijian; Qiu, Jiguo; Xu, Jianhong; Hong, Qing
Abstract: Salicylate is a typical aromatic compound widely distributed in nature. Microbial degradation of salicylate has been well studied and salicylate hydroxylases play essential roles in linking the peripheral and ring‐cleavage catabolic pathways. The direct hydroxylation of salicylate catalyzed by salicylate‐1‐hydroxylase or salicylate‐5‐hydroxylase has been well studied. However, the CoA mediated salicylate 5‐hydroxylation pathway has not been characterized in detail. Here, we elucidate the molecular mechanism of the reaction in the conversion of salicylate to gentisate in the carbaryl‐degrading strain Rhizobium sp. X9. Three enzymes (salicylyl‐CoA ligase CehG, salicylyl‐CoA hydroxylase CehH and gentisyl‐CoA thioesterase CehI) catalyzed the conversion of salicylate to gentisate via a route, including CoA thioester formation, hydroxylation and thioester hydrolysis. Further analysis indicated that genes cehGHI are also distributed in other bacteria from terrestrial environment and marine sediments. These genomic evidences highlight the role of this salicylate degradation pathway in the carbon cycle of soil organic compounds and marine sediments. Our findings of this three‐step strategy enhanced the current understanding of CoA mediated degradation of salicylate. Abstract : The CoA mediated salicylate catabolic pathway was found in Rhizobium sp. X9. Three enzymes including salicylyl‐CoA ligase CehG, salicylyl‐CoA hydroxylase CehH, and gentisyl‐CoA thioesterase CehI involved in this pathway were studied in detail. Sequence analysis indicated that genes cehGHI are also distributed in other bacteria from terrestrial environment and marine sediments.